Haemonchus contortus as a paradigm and model to study anthelmintic drug resistance. Issue 12 (2nd September 2013) - GILLEARD, JOHN S.
SUMMARY: Anthelmintic resistance is a major problem for the control livestock parasites and a potential threat to the sustainability of community-wide treatment programmes being used to control human parasites in the developing world. Anthelmintic resistance is essentially a complex quantitative trait in which multiple mutations contribute to the resistance phenotype in an additive manner. Consequently, a combination of forward genetic and genomic approaches are needed to identify the causal mutations and quantify their contribution to the resistance phenotype. Therefore, there is a need to develop genetic and genomic approaches for key parasite species identified as relevant models. Haemonchus contortus, a gastro-intestinal parasite of sheep, has shown a remarkable propensity to develop resistance to all the drugs used in its control. Partly because of this, and partly because of its experimental amenability, research on this parasite has contributed more than any other to our understanding of anthelmintic resistance. H. contortus offers a variety of advantages as an experimental system including the ability to undertake genetic crosses; a prerequisite for genetic mapping. This review will discuss the current progress on developing H. contortus as a model system in which to study anthelmintic resistance.